Adaptive Interpersonal Communication Model for Multicultural Families in Indonesia’s Digital Era: A Literature Review - Fairus; Jarnawi; Arif Ramdan Sulaeman; Fakhri; Nursaady Ibrahim (FAKULTAS DAKWAH UIN SALATIGA, 2026)
The digital era has changed the method of communication and interaction within families and multicultural groups in Indonesia, thus creating new challenges in building effective interpersonal communication. On that basis, the research aims to develop an adaptive interpersonal communication model for multicultural families.​​​ By conducting an analysis literature through approach content thematic through the stages of coding, categorization, synthesis findings, and development framework theoretical to various publication scientific 2021-2025 period which discusses family interpersonal communication, communication multicultural, and adaptation digital technology, this qualitative research based on literature studies identifies that the challenges main interpersonal communication of multicultural families in the digital era includes gap digital literacy, preservation mark culture, complexity interpretation meaning, and management platform communication. Family multicultural development strategy adaptation, structural, functional, and relational, to overcome challenges in those factors. Success adaptation covers digital literacy, quality family connections, accessibility to technology, the presence of digital mentors, and organizational capability. The Adaptive Interpersonal Communication Model (ADAC) was developed with four components integrated: Assessment, Adaptation, Application, and Evaluation. This model provides a framework for helping families to build communication harmoniously, integrating digital technology and the diversity of values and cultures in the multicultural context of Indonesia.